Analysis of the Importance of BUMDes Management in Village Development - Sari, Mei Indah; Sopanah, Ana; Bahri, Syamsul (Clean and Sustainable Production, 2024)
Managing BUMDes village finances is important because in managing BUMDes finances there are principles that need to be taken into account. Management of managed village finances must be carried out openly to create transparency. It is important for the public and government to know about the financial management of Village-Owned Enterprises (BUMDes) in Dengkol Village. Because, finances from Village-Owned Enterprises (BUMDes) in Dengkol Village will be allocated for village development since the formation of Village-Owned Enterprises (BUMDes) in Dengkol Village began, so this must be done based on the procedures implemented. The research uses qualitative descriptive analysis. Data analysis method by means of data reduction, data presentation, and drawing conclusions. The research results show that financial management of Village-Owned Enterprises (BUMDes) in Dengkol Village has been implemented by applying cooperative, participatory, emancipatory, transparent, accountable and sustainable principles. In managing the finances of BUMDes Dengkol, the community has not been able to optimally manage this BUMDes, because there is still a lack of human resources who can participate in the management of BUMDes Dengkol.